Pengaruh Pendidikan Kewirausahan Terhadap Minat Berwirausaha dan Motivasi Berwirausaha - Muh Fahrurrozi; Huzain Jailani; Yogi Rahmadi Putra; Danang Prio Utomo (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2020)
This study aims to determine (1) the magnitude of the influence of entrepreneurship education on interest in entrepreneurship (2) the magnitude of the influence of entrepreneurship education on entrepreneurial motivation. In this study using a quantitative approach. The population in this study were 432 students. The sampling technique in this research is Simple Random Sampling technique. The variables of this research are entrepreneurship education (X) as the independent variable and the dependent variable is interest in entrepreneurship (YÄ±) and entrepreneurial motivation (Y2). The data collection techniques used were questionnaires. Data analysis techniques include variable descriptive analysis and analysis prerequisite test. The type of research used in this research is quantitative descriptive research, which is a method or approach in which the symptoms under study are analyzed using statistical assistance or numbers or computer assistance with the SPSS 16.0 for windows program. The results of the research show that (1) There is a positive influence of entrepreneurship education on interest in entrepreneurship, indicated by the magnitude of the Fcount of 28.577 with a significance of 0.000. (2) There is a positive effect of entrepreneurship education on entrepreneurial motivation as indicated by the value of Fcount 60.539 with a significance of 0.000